2015
DOI: 10.1042/cs20140749
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole in steroid-sensitive nephrotic syndrome: usefulness in adult patients and laboratory insights into mechanisms of action via direct action on the kidney podocyte

Abstract: Minimal change nephropathy (MCN) is the third most common cause of primary nephrotic syndrome in adults. Most patients with MCN respond to corticosteroid therapy, but relapse is common. In children, steroid-dependent patients are often given alternative agents to spare the use of steroids and to avoid the cumulative steroid toxicity. In this respect, levamisole has shown promise due to its ability to effectively maintain remission in children with steroid-sensitive or steroid-dependent nephrotic syndrome. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…(R)Mycophenolate (MMF) or cyclophosphamide (CTX) for the same duration are alternatives, particularly for patients who cannot tolerate high dose corticosteroids. Levamisole may also be considered For steroid‐resistant MCD, addition of calcineurin inhibitor can be considered.…”
Section: Glomerulonephritidesmentioning
confidence: 99%
“…(R)Mycophenolate (MMF) or cyclophosphamide (CTX) for the same duration are alternatives, particularly for patients who cannot tolerate high dose corticosteroids. Levamisole may also be considered For steroid‐resistant MCD, addition of calcineurin inhibitor can be considered.…”
Section: Glomerulonephritidesmentioning
confidence: 99%
“…Levamisole was shown to be effective in reducing the frequency of relapses in adult patients with SSNS [91], which was supported by a systematic review of RCTs [92]. In children with SSNS, a recent open-label RCT showed that levamisole had comparable and satisfactory efficacy compared to MMF in maintaining sustained remission [93].…”
Section: Levamisolementioning
confidence: 88%
“…Levamisole is a synthetic imidazole derivative which, instead of suppressing immunity, enhances humoral immune response and macrophage activation [89] and induces type 1 (Th1) and type 2 (Th2) T-cell responses through enhancing IL-18 activity [90]. In a human podocyte model, levamisole was shown to induce expression of glucocorticoid receptor, and it has been suggested that glucocorticoid signalling is a critical target of levamisole action [91].…”
Section: Levamisolementioning
confidence: 99%
“…Jiang reported that levamisole induced expression of glucocorticoid receptor (GR) and activated GR signaling in podocytes. Furthermore, levamisole was able to protect against podocyte injury in a puromycin aminonucleoside (PAN)-treated cell model [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that levamisole reduces the frequency of relapses and corticosteroid doses in children with FRNS and SDNS [816]. In most cases levamisole therapy did not cause any severe side effects.…”
Section: Introductionmentioning
confidence: 99%